Analyzing and interpreting qualitative research after the interview - Vanover, Charles; Mihas, Paul; Saldana, Johnny (SAGE Publications, Inc, 2021)
"This text provides comprehensive coverage of the key methods for analyzing, interpreting, and writing up qualitative research in a single volume, and drawing on the expertise of major names in the field. Covering all the steps in the process of analyzing, interpreting, and presenting findings in qualitative research, the authors utilize a consistent chapter structure that provides novice and seasoned researchers with pragmatic, "how-to" strategies. Each chapter introduces the method; uses one of the authors' own research projects as a case study of the method described; shows how the specific analytic method can be used in other types of studies; and concludes with questions and activities to prompt class discussion or personal study"